2018
DOI: 10.1093/schbul/sby111
|View full text |Cite
|
Sign up to set email alerts
|

Associations and Heritability of Auditory Encoding, Gray Matter, and Attention in Schizophrenia

Abstract: Present findings indicated that the 3 SZ endophenotypes examined are not isolated markers of pathology but instead are connected. The pattern of auditory encoding group differences and the pattern of brain function-structure associations differ as a function of brain region, indicating the need for regional specificity when studying these endophenotypes, and with the presence of left STG function-structure associations in HC and UR but not in SZ perhaps reflecting disease-associated damage to gray matter that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Because auditory hallucinations are a prominent manifestation of schizophrenia, many electroencephalography and MEG studies of auditory encoding have been performed, examining activity in the superior temporal gyri, including time-frequency plots of total power, and inter-trial coherence or phase-locking plots. Chen et al (2019) found that control subjects had stronger auditory encoding activity in superior temporal gyri than patients with schizophrenia, and showed that unaffected relatives of the patients had responses which were similar to control patients in the superior temporal gyri, but were abnormal and similar to the patients, in the left superior frontal gyrus. Some but not all MEG studies show abnormal auditory gating in patients with schizophrenia: presented with two clicks 500 ms apart, normal subjects show decreased auditory activation response to the second click compared to the first, indicating habituation to the stimulus.…”
Section: Magnetoencephalographymentioning
confidence: 90%
“…Because auditory hallucinations are a prominent manifestation of schizophrenia, many electroencephalography and MEG studies of auditory encoding have been performed, examining activity in the superior temporal gyri, including time-frequency plots of total power, and inter-trial coherence or phase-locking plots. Chen et al (2019) found that control subjects had stronger auditory encoding activity in superior temporal gyri than patients with schizophrenia, and showed that unaffected relatives of the patients had responses which were similar to control patients in the superior temporal gyri, but were abnormal and similar to the patients, in the left superior frontal gyrus. Some but not all MEG studies show abnormal auditory gating in patients with schizophrenia: presented with two clicks 500 ms apart, normal subjects show decreased auditory activation response to the second click compared to the first, indicating habituation to the stimulus.…”
Section: Magnetoencephalographymentioning
confidence: 90%
“…Previous magnetic resonance imaging (MRI) studies were reviewed, the results have explicitly suggested certain brain areas in relation to cognitive impairment (27). For instance, several studies exhibited that the decreased cortical thickness in the frontal and temporal lobes may be correlated with cognitive function abnormalities, mainly performed on attention (28). Another study showed that the loss of cortical thickness in the right lateral orbitofrontal may be related to attention and visual learning (29).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, some researchers have reported a similar pattern of cognitive deficits between patients with schizophrenia and the first-degree relatives, including working memory, set shifting, and prepotent response (Johnstone et al, 2002; Brewer et al, 2005; Snitz et al, 2006). Similarly, a M100 magnetoencephalography study found greater left SFG M100 activity in not only patients with schizophrenia but also unaffected relatives (Chen et al, 2018). This shared auditory encoding abnormality indicated a compensatory adjustment by overactivating dorsal auditory pathway (Chen et al, 2013) and could also be regarded as a potential endophenotype.…”
Section: Discussionmentioning
confidence: 91%